Kesesuaian Pemilihan Kata Kunci Penulis pada Publikasi Sustainable Development Goals - Fauzi, Syahrul; Ermawati, Netti; Nurjanah, Umi; Sadida, Qualan (Media Informasi, 2024)
The selection of appropriate keywords in the abstract of a scientific work is essential because it can reflect the content of the work. Keywords play an essential role in the documentation system of information collection and help in the process of rediscovering the information that has been collected. Therefore, it is very crucial to include appropriate keywords in the abstract of scientific papers. This study aims to evaluate the suitability between the keywords in the Faculty of Psychology, Universitas Gadjah Mada's publications registered in Scopus from 2018-2023 with query SDG. From 146 publication titles, 55 are related to SDGs. However, 7 of the 55 SDGs publications did not have keywords, so only 48 titles were analysed. The keywords of the 48 publications were tabulated and analyzed, then compared with the SDG query Scopus. The results showed that many authors used different keyword concepts/terms despite the same article topic. 85.4% of the keywords created by the authors were by the SDG Scopus query, while the other 14.6% were not.